CHANGES IN THE DYNAMICS AND DEMOGRAPHIC STRUCTURES OF THE ROMANIAN URBAN POPULATION. AN OVERVIEW OF THE POST-COMMUNIST PERIOD - BIANCA MITRICĂ (Revue Roumaine de Géographie)
In the present period Romania’s urban system is undergoing a process of restructuring, the urban phenomenon acquiring new dimensions and characteristics. Thus, the industrial town – the representative type of urban settlement, has largely been replaced by the polyfunctional and services type, a trend that met the country’s major economic and social-political targets, set early in the Third Millennium, in line with Romania’s integration into the European urban system. Another trend, this time in rural-urban evolution, was to raise communes, viewed as local polarisation cores, to town status. Consequently, between 2003 and 2011, a number of 53 settlements (out of the 60 given town rank after 1989) were raised to this position. Although in the postwar period and up to the last 20th-century decade the share of Romania’s urban population/total population was steadily growing (55% in 1997), yet the annual average growth rate was gradually declining, the numerical increase of townspeople slowing down. Since in the 1990–2011 interval, the urban population would even decrease, also the level of urbanization was slightly dropping (54%). The demographic structures themselves suffered some changes in that the female population increased, the young one decreased, while mature and elderly people became evermore numerous.